O trabalho que faz sofrer, o sofrimento que faz trabalhar: o trabalho dos técnicos-administrativos nas universidades públicas - Roldão, João Marcos (2025)
This dissertation aimed to understand how the psychological suffering experienced by technical-administrative staff at public universities is instrumentalized by New Public Management. Grounded in the theoretical framework of the Psychodynamics of Work, the study starts from the hypothesis that defensive strategies, far from being mere side effects of precarization, can be appropriated as mechanisms for intensifying and controlling work in a context marked by the dismantling of labor conditions, workforce, and career structures. The research was conducted at two public universities through semi-structured interviews with eight technical-administrative staff experiencing work-related suffering. The data were analyzed using Work Clinical Analysis and Thematic Content Analysis. Examination of institutional structures and participant narratives revealed that experiences of suffering emerged in various forms of organizational violence and were intensified by managerial strategies that operationalized the dialectic of exclusion/inclusion, the banalization of social injustices, and subjective precarization. Furthermore, practices such as moral harassment, work overload, academic authoritarianism, and the erosion of technical-administrative identity not only produced suffering but also reinforced performance and submission to alienated labor, even in the face of increasing precarization. The dissertation concludes that, within universities influenced by New Public Management, the instrumentalization of suffering becomes a low-cost, high-return mechanism for maintaining academic productivism – which, in turn, is elevated to a survival imperative amid budget cuts and growing dependence on private funding and support from research funding agencies.